2009
DOI: 10.1177/0883073809332695
|View full text |Cite
|
Sign up to set email alerts
|

Pharyngeal-Cervical-Brachial Variant of Pediatric Guillain-Barré Syndrome With Antecedent Acute Hepatitis A Virus Infection

Abstract: Pharyngeal-cervical-brachial weakness is considered a variant of Guillain-Barré syndrome with limited oropharyngeal, neck, and upper limb muscle involvement. The authors report on a 7-year-old boy, who developed pharyngeal-cervical-brachial type of Guillain-Barré syndrome following an antecedent episode of acute hepatitis A virus infection, 2 weeks prior to admission. The presentation was characterized by acute onset dysphagia, loss of head control, and bilateral arm weakness. The diagnosis was confirmed by ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…5) A uniformly good outcome of the neuropathic symptoms is independent of the level of ALT, which corresponds to the severity of liver dysfunction (10). Most electrodiagnostic studies were compatible with an acquired demyelinating polyradiculoneuropathy, but a few cases showed dominant axonal involvement i.e., acute motor axonal neuropathy (AMAN) (11,12). The prognosis of HA virus-associated GBS was favorable, both in earlier reports (management with supportive care only) and in more recent reports (treatment with either intravenous immunoglobulin [IVIG] or plasmapheresis) (9).…”
Section: Discussionmentioning
confidence: 99%
“…5) A uniformly good outcome of the neuropathic symptoms is independent of the level of ALT, which corresponds to the severity of liver dysfunction (10). Most electrodiagnostic studies were compatible with an acquired demyelinating polyradiculoneuropathy, but a few cases showed dominant axonal involvement i.e., acute motor axonal neuropathy (AMAN) (11,12). The prognosis of HA virus-associated GBS was favorable, both in earlier reports (management with supportive care only) and in more recent reports (treatment with either intravenous immunoglobulin [IVIG] or plasmapheresis) (9).…”
Section: Discussionmentioning
confidence: 99%
“…This review includes only GBS patients with confirmed acute HAV infection (positive serum anti-HAV-IgM antibodies) ( Table 1) [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42]. For this review, an association was presumed based on [43]: (a) the temporal sequence of events (intervalb 4 weeks between antecedent infection and onset of neuropathy); (b) absence of other trigger events (e.g., no known coexistent infections); (c) analogy (i.e., other infections are firmly linked to GBS [44]), and (d) biological plausibility (i.e., infections may effect an immune response against one or more peripheral nerve antigens).…”
Section: Guillain-barré Syndromementioning
confidence: 99%
“…Besides limb paresis, some patients also suffered bifacial palsy [27][28][29][30]32,37], unilateral facial palsy [40], bulbar paresis [31,37], and dyspnea that required ventilatory support [37,[39][40][41]. Sensory ataxic [26,35] and pharyngo-cervical-brachial [42] variants of GBS were described. The severity of hepatitis, judged by range of abnormal liver function tests, was typical of other cases of hepatitis A.…”
Section: Guillain-barré Syndromementioning
confidence: 99%
See 2 more Smart Citations